Clinical features of hyperprolactinemia in children: modern methods of diagnosis and treatment - A.E. Abaturov; A.O. Nikulina; T.D. Alieinykova (Zaslavsky O.Yu., 2022)
Hyperprolactinemia is a common endocrine disease that can be associated with significant morbidity and disability in the population. A systematic review of literature sources on the diagnosis and treatment results in patients with hyperprolactinemia, including drug-resistant micro- and macroadenomas of the pituitary gland, was carried out in order to highlight the most significant practical recommendations. The purpose of this literature review is to provide algorithms for differential diagnosis and clinical observation of patients, to compare the efficacy and side effects of drugs, surgeries, and radiation therapy in the treatment of hyperprolactinemia. Prolactinomas are the most common pituitary adenomas in older children. Their share in the structure of pituitary adenomas is about 50 %. The clinical picture depends on the age, sex of the child, volume and characteristics of tumor growth. The leading clinical manifestations of hyperprolactinemia are disorders of the reproductive system, including signs of the development of secondary hypogonadotropic hypogonadism, sexual dysfunction, psychoemotional disorders, and endocrine and metabolic disorders. The main criterion for the diagnosis of hyperprolactinemia is the concentration of prolactin in the blood serum, which is above the upper limit of the physiological norm. The primary step in the treatment of patients with pituitary macroadenoma is to control the compression effects of the tumor, including compression of the optic chiasm, followed by restoration of gonadal function. The main areas of treatment for hyperprolactinemia are restoration and maintenance of the normal function of the gonads; restoration of fertility; prevention of osteoporosis. Dopamine receptor agonists are the gold standard in the treatment of hyperprolactinemia. However, some people do not respond satisfactorily to these drugs. In this case, in the presence of pituitary tumors, in addition to drug treatment, surgery and radiation therapy are used. But surgery and radiation therapy are not the primary methods of choice for the management of patients with prolactin-secreting pituitary adenomas; first of all, preference is given to drug therapy. The prognosis of the course of prolactinomas is favorable and is based on the results of dynamic observation and the presence of markers of the aggressiveness of this adenoma.